Hasil Belajar Siswa Kelas XI pada Mata Pelajaran PAI di SMAN 1 Bonjol Kabupaten Pasaman - Putri‎, Frastika; Jasmienti, Jasmienti (Indonesian Research Journal on Education, 2023)
This research is motivated by phenomena that occur in the field, that there are several factors that cause low learning outcomes for students in student PAI subjects that cause PAI learning outcomes to be less than optimal. At the end of the semester, students whose scores are still below the minimum completeness standard (KKM), low learning outcomes for students are a form of problem related to student learningoutcomes. The problems encountered were low scores obtained by students. This low score is seen from the results obtained by students at the end of the meeting, the teacher retests the material that has been studied. From that assessment, it was found that there were 10 people whose scores were below the KKM.The KKM set by the school is 75. From the problems that have been seen, that is what motivated the researchers to look for the Learning Outcomes of Class XI Students in PAI Subjects at SMA N 1 Bonjol, Pasaman Regency. Therefore, this study aims to reveal the learning outcomes of students in Islamic religious education lessons at SMA N 1 Bonjol. This type of research is descriptive qualitative research, namely data analysis that emphasizes meaning, reasoning, definition, or relating to everyday life and isdescriptive in nature, namely describing what is about the object being studied. In this study, the number of students in class XI IPA 2 which will be studied is 10 students, with one teacher of PAI subjects. Data collection techniques through interviews from facts or events in the field. The results of the study regarding the factors that cause low learning outcomes for students in Islamic religious education lessons at SMA N 1 Bonjol consist of concentration factors, interest factors, teacher delivery factors, afternoon schedule factors, and learning factors.